2021
DOI: 10.1007/s40121-021-00448-0
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Sexualized Substance Use and Other Risk Practices on HCV Microelimination in gbMSM Living with HIV: Urgent Need for Targeted Strategies. Results of a Retrospective Cohort Study

Abstract: Introduction:The objective of the present study is to describe the incidence of recently acquired hepatitis C (RAHCV) in a large cohort of people living with HIV (PLWHIV) and sexualized drug use and other related risk behaviours. Methods: Observational study including all PLWHIV with a RAHCV episode between June 2005 and December 2019 at the Hospital Clinic of Barcelona, Spain. Incidence of RAHCV was determined per person calendar year (py) in those patients who were HCV RNA negative. Data were collected on hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…Based on this, variables other than sharing injection materials, such as high-risk sexual practices, may be related risk factors for HCV infection. This hypothesis is supported by other publications (Berenguer et al, 2019;Martínez-Rebollar et al, 2015), and individuals who engage in chemsex are a target population to tailor strategies to achieve HCV microelimination (Martínez-Rebollar et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…Based on this, variables other than sharing injection materials, such as high-risk sexual practices, may be related risk factors for HCV infection. This hypothesis is supported by other publications (Berenguer et al, 2019;Martínez-Rebollar et al, 2015), and individuals who engage in chemsex are a target population to tailor strategies to achieve HCV microelimination (Martínez-Rebollar et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…These results are in contrast with those from models predicting increased nondiagnosed cases of hepatitis C in Spain during the COVID-19 epidemics [24] but they are in accordance with recent real data from the USA [25]. De novo hepatitis C diagnosis in our setting has been more commonly linked to high-risk sexual practices and sexualized substance use [26]. It is possible that these practices may have been more affected by the epidemic than other sexual encounters.…”
Section: Discussionsupporting
confidence: 72%
“…Fourth, compared with the suboptimal efficacy and tolerance of IFN, the awareness of potent and safe DAAs to manage HCV reinfection in HIV-positive patients may reduce vigilance for the unsafe sex and shared injections that potentiate reinfection [ 36–39 ]. As observed in our cohort, studies from Germany, the Netherlands, and Spain indicated that the risk of HCV reinfection tended to increase in the era of DAAs among MSM with high-risk sexual behaviors regardless of HIV status [ 17 , 20 , 40 ].…”
Section: Discussionsupporting
confidence: 70%
“…Although the risk of HCV reinfection of our HIV-positive patients was much higher than that of the reference patients, we found that no baseline factors predicted HCV reinfection [ 21 ]. Multiple sex partners, unprotected anal intercourse, group sex, sharing sex toys, and amphetamine abuse in HIV-positive MSM and ongoing use of cocaine, methamphetamine, or heroin injection in HIV-positive PWID after achieving SVR were highly associated with HCV reinfection; these factors were evident in our HIV-positive patients with HCV reinfection [ 17 , 20 , 24 , 30 ]. Furthermore, studies also showed that a new diagnosis of sexually transmitted infection or syphilis during post-SVR 12 follow-up was highly associated with risk of HCV infection among HIV-positive patients [ 23 , 31 ].…”
Section: Discussionmentioning
confidence: 97%